Proposta metodológica e análise de viabilidade econômica de programa de pagamento por serviços ambientais em bacias hidrográficas para controle de inundações - Campos, Rosiâny Possati (2017)
Disordered urban growth leads to the occupationof areas that should be protected by law, directly affecting landuse patterns.When the needfor preservation orconservation of the environmentis disregarded, the natural landscapechangesandnegatively affects the natural systems functions, frequentlyleading to more severe floods. The challenge of reversingthe degradation framework makes it necessary to create feasible solutions.Using the economic instrument defined as Payment for Environmental Service (PES) can encourage the environmental preservation or recovery, enabling actionsin this direction. This work proposes the useof this economic instrument for recoveringand conserving areas ofenvironmental interestina river basin. Taking the fluvial space as reference,and through actions of reforestation it is possible to induce the environmental servicefor flood control. In order to apply the presented methodology, the Sesmaria River Basin (Resende, RJ, Brazil)wasused as acase study,individualizing the anthropic actionsthat have taken place over decades andthe consequences of the abovementioned disordered occupation in the basin, leading to the aggravation of the floodevents and theconsequent public and private losses.The evaluationof the damages caused by such events and that are possible to avoid, or at leasttominimize in a given measure, isused to quantify the economicbenefits with the implantation of the PES.Through thisprocedure, it ispossibleto create financing conditions to stop and reverse thedegradation of the river basin andto promotepartial control of floods, reducing urban losses.